(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the development of pedagogical reflective skills in prospective primary school teachers. It also analyzes the main components of this skill - self-awareness, analytical thinking, and self-management skills - and highlights their importance in the professional development of teachers.